Short‐ and long‐term effects of a community‐based suicide prevention program: A Hong Kong experience. Issue 3 (10th February 2022) - Yeung, Cheuk Yui; Morgan, Peter R.; Lai, Carmen Chui Shan; Wong, Paul Wai Ching; Yip, Paul Siu Fai
Abstract: Background: A multidisciplinary, multilayer, community‐based suicide prevention program (2008–2012) was implemented in the Eastern District, Hong Kong. This article documents the program and reports on short‐ and longer‐term program evaluation. Methods: Characteristics and rates of self‐harm/suicidal behaviors and suicide deaths by age group and gender in the Eastern District before, during, and after the intervention were calculated and compared with the rest of Hong Kong, using Kruskal–Wallis and chi‐squared tests, and Jonckheere–Terpstra and Cochran–Mantel–Haenszel tests for trend analyses. Results: The program impacts varied by age and gender subgroups. Suicide rates in the Eastern District were lower compared to the rest of Hong Kong during the intervention period. They slowly rebounded after the intervention ceased; nevertheless, they remained lower than the rest of Hong Kong until 2016. The rates of self‐harm continuously dropped and remained lower than the rest of Hong Kong. During the intervention period in the Eastern District, the age of people who died by suicide increased; more deaths occurred from jumping and fewer by charcoal burning. Conclusions: The program coincided with the lowered self‐harm and suicide rates after the implementation. Some of the strategies need to be rebooted or routinely and continuously implemented to ensure the sustainability.